2013
DOI: 10.1179/1743278213y.0000000114
|View full text |Cite
|
Sign up to set email alerts
|

Studying inhomogeneity of organic coatings using wire beam multielectrode and physicomechanical testing

Abstract: The effect of thickness, curing temperature and solvent on the structural inhomogeneity of several types of organic coatings has been investigated. The local distribution of electrochemical resistance was studied using a wire beam multielectrode array, while the inhomogeneity at a larger scale was examined using ,3 cm 2 area detached coatings. Physicomechanical tests were also employed to address the structural changes occurring because of variation in curing temperature and the type (or absence) of solvent. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…It was believed that water uptake into the film controlled the "I" type conduction whereas ion uptake into the film controlled "D" type conduction. More recently Jamali and Mills studied the electrical properties of coatings using the wire beam electrode at millimetre spatial resolution 8 and concluded that the majority of film area was of "I" type.…”
Section: Coating Heterogeneitymentioning
confidence: 99%
“…It was believed that water uptake into the film controlled the "I" type conduction whereas ion uptake into the film controlled "D" type conduction. More recently Jamali and Mills studied the electrical properties of coatings using the wire beam electrode at millimetre spatial resolution 8 and concluded that the majority of film area was of "I" type.…”
Section: Coating Heterogeneitymentioning
confidence: 99%
“…Saturated calomel electrode (SCE) was used as reference electrode in all experiments. Resistance value of coatings was defined prior to testing using a DC electrometer in a two electrode arrangement with a single U-cell and two SCEs (for details see reference [34]). Noise measurement was conducted at 2 Hz sampling frequency with a total of 512 data points collected in 256 seconds.…”
Section: Physical Modelmentioning
confidence: 99%
“…The SCE impedances, typically in the order of 10 4 ohm is negligible compared to high impedance of organic coatings and therefore considered insignificant. This method of impedance measurement has been used and described in the literature a number of times [14,25,34]. The DC resistance was measured with first 1 mM KCl and then 3.5 M KCl solutions to identify the conduction type of each piece.…”
Section: Measuring D Type Percentagementioning
confidence: 99%